2012
DOI: 10.1155/2012/540681
|View full text |Cite
|
Sign up to set email alerts
|

Serum FSH Levels in Coasting Programmes on the hCG Day and Their Clinical Outcomes in IVF ± ICSI Cycles

Abstract: Introduction. Coasting is the most commonly used strategy in prevention of severe OHSS. Serum FSH levels measurements during coasting may aid in optimizing the duration of coasting. Objective(s). To study live birth rates (LBRs), clinical pregnancy rates (CPRs), and optimal duration of coasting based on serum FSH levels on the hCG day. Materials and Methods. It is a retrospective study performed between 2005 and 2008 at Barts and The London Centre for Reproductive Medicine, NHS Trust, London, UK, on 349-coaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…the current study's centre, based on 350 coasted cycles, did not find that serum FSH <5 IU/l discriminated between cycles resulting in clinical pregnancy or live birth compared with higher serum FSH, but no live birth was found in cycles when serum FSH fell below 2.5 IU/l on the HCG day at the end of coasting (Vitthala et al, 2012). The differences in results between the above studies could be explained by the different study populations and study designs.…”
Section: -Specificitycontrasting
confidence: 74%
See 2 more Smart Citations
“…the current study's centre, based on 350 coasted cycles, did not find that serum FSH <5 IU/l discriminated between cycles resulting in clinical pregnancy or live birth compared with higher serum FSH, but no live birth was found in cycles when serum FSH fell below 2.5 IU/l on the HCG day at the end of coasting (Vitthala et al, 2012). The differences in results between the above studies could be explained by the different study populations and study designs.…”
Section: -Specificitycontrasting
confidence: 74%
“…A recent study estimated the best discriminative value of FSH at HCG injection in predicting CPR to be 4.9 IU/l (Erman Akar and Oktay, 2009). A recent paper from the current study centre indicated no live births occurring when the FSH fell below 2.5 IU/l on the day of HCG injection (Vitthala et al, 2012). This study aimed to determine if total fall or percentage fall in serum FSH from the start to end of coasting is correlated with clinical outcomes, primarily LBR and CPR.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Exogenous human chorionic gonadotrophin (hCG) has a major role in OHSS development via increasing capillary permeability (1). There are many treatment varients such as cycle cancel, witholding HCG, coasting, intravenous albumin and dopamin agonist administration to reduce incidince and severity of OHSS in high risk patient (2). Coasting, one of the most used methods, refers to witholding exogenous gonodotropine usage and delaying the administration of hCG in high risk cycles until serum estradiol falls into an acceptable range (typically less than 2500 to 3000 pg/mL) (2-7).…”
Section: Introductionmentioning
confidence: 99%
“…Coasting, one of the most used methods, refers to witholding exogenous gonodotropine usage and delaying the administration of hCG in high risk cycles until serum estradiol falls into an acceptable range (typically less than 2500 to 3000 pg/mL) (2-7). Coasting decreases FSH levels and causes granulosa cell apoptosis and inhibition of proliferation via luteinazition (2,6). As a conse-quence, coasting prevent onset of OHSS (2,8).…”
Section: Introductionmentioning
confidence: 99%